Strategi Pengelolaan Wisata Susur Sungai Mahakam Berbasis Ekowisata Di Samarinda - Dwiyono Rudi Susanto; Amin Kiswantoro (Journal of Tourism and Economic, 2020)
This research aims to determine the right strategy in managing the Mahakam River tourist destinations in an ecotourism. This is because the Mahakam River has the potential to be managed ecotourically, because in addition to nature tourism on the Mahakam River there are also dolphins, which are endemic animals of the Mahakam River which are currently small in number and included in the category of endangered animals. This research is a qualitative research with non probability sampling technique, then the data obtained are analyzed using SWOT analysis. The results of this study obtained several strategies that can be applied in the Mahakam River tourist destination to be managed ecotourism. These strategies include (1) conducting training on ecotourism for HR managing the Mahakam River, (2) minimizing the use of ships that produce a lot of air pollution, (3) organizing HR training for waste management, particularly in tourist sites and surroundings, (4) making the Mahakam River a conservation place for dolphins, (5) educating all parties, both managers and tourists, to care for the environment.